2016
DOI: 10.1038/cddis.2016.125
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA related to periodontitis interacts with miR-182 to upregulate osteogenic differentiation in periodontal mesenchymal stem cells of periodontitis patients

Abstract: Periodontitis impairs the osteogenic differentiation of human periodontal mesenchymal stem cells (hPDLSCs), but the underlying molecular mechanisms are still poorly understood. Long noncoding RNAs (lncRNAs) have been demonstrated to have significant roles under both physiologic and pathological conditions. In this study, we performed comprehensive lncRNA profiling by lncRNA microarray analysis and identified a novel lncRNA, osteogenesis impairment-related lncRNA of PDLSCs from periodontitis patients (lncRNA-PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
148
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 51 publications
7
148
0
Order By: Relevance
“…Recently, accumulating lncRNAs have been demonstrated as endogenous ceRNAs for specific miRNAs and regulate their function; for instance, in 2016, Lv et al () revealed that lncRNA Unigene56159 promotes epithelial–mesenchymal transition by acting as a ceRNA of miR‐140‐5p in hepatocellular carcinoma cells; and Wang et al () reported that lncRNA related to periodontitis interacts with miR‐182 to upregulate osteogenic differentiation in periodontal mesenchymal stem cells of periodontitis patients. In our present study, we provide evidence that PVT1 may also function as ceRNA to competitively sponge miR‐448 and affect its distribution on specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating lncRNAs have been demonstrated as endogenous ceRNAs for specific miRNAs and regulate their function; for instance, in 2016, Lv et al () revealed that lncRNA Unigene56159 promotes epithelial–mesenchymal transition by acting as a ceRNA of miR‐140‐5p in hepatocellular carcinoma cells; and Wang et al () reported that lncRNA related to periodontitis interacts with miR‐182 to upregulate osteogenic differentiation in periodontal mesenchymal stem cells of periodontitis patients. In our present study, we provide evidence that PVT1 may also function as ceRNA to competitively sponge miR‐448 and affect its distribution on specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…PDLSCs are used in periodontal tissue regeneration engineering, periodontal defect repair and gene therapy and have multidirectional differentiation and self‐renewal potential. Because of the development of high‐throughput sequencing technologies, an increasing number of non‐coding RNAs have been found to play an important role in the progression of chronic inflammatory diseases, such as rheumatoid arthritis and periodontitis . By constructing a WGCNA network and calculating the co‐expression relationships between molecules, we can identify the hub genes in the module and provide an overview of the hub gene‐related expression profiles and gene function relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lncRNA can act as a miRNA sponge that regulates miRNA‐targeted mRNA expression. It has been reported that lncRNA‐POIR promotes the expression of FoxO1 through the competitive binding of miR‐182 to increase bone formation by PDLSCs . Peng et al found that lncRNA‐ANCR can upregulate Notch2 by competitively binding miRNA‐758 and inhibiting bone formation by periodontal ligament stem cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Huang et al revealed a H19/miR-675/TGF-b1/Smad3/HDAC pathway in regulating osteogenic differentiation of human MSCs. 15 In addition, lncRNA-POIR 16 and MEG3 17 were reported to regulate osteogenic differentiation through different mechanisms, whereas knockdown of HoxA-AS3 expression enhanced osteogenic differentiation and osteogenesis markers expression in MSCs. 18 These studies implied that lncRNAs both positively and negatively control the differentiation state of stem cells.…”
mentioning
confidence: 99%